miR‐647 inhibits glioma cell proliferation, colony formation and invasion by regulating HOXA9 - Qin, Kun; Tian, Ge; Chen, Guangzhong; Zhou, Dong; Tang, Kai (The journal of gene medicine, 2020)
Background MicroRNA‐647 (miR‐647) has been reported to regulate tumor development, although its role in glioma remains unclear. Methods miR‐647 expression in glioma cells and normal cells was measured using a quantitative real‐time polymerase chain reaction. The effects of miR‐647 expression on glioma cell proliferation, cell apoptosis, colony formation and cell invasion were measured using a cell counting kit‐8 assay, flow cytometry, a colony formation assay and a transwell invasion assay. Luciferase activity reporter and western blot assays were conducted to explore whether homeobox A9 (HOXA9) was a direct target of miR‐647. Results We found that miR‐647 expression was downregulated in glioma cell lines compared to the normal cell line. Overexpression of miR‐647 inhibits glioma cell proliferation, colony formation and cell invasion, although it promotes apoptosis in vitro. HOXA9 was validated a direct target of miR‐647 and the overexpression of HOXA9 reversed the effects of miR‐647 on glioma cell behavior. Conclusions The identification of the miR‐647/HOXA9 axis will advance our understanding underlying glioma progression and provide novel therapeutic targets for glioma treatment.